Four new cavernicolous species of the genus Acanthophorella Antić & Makarov, 2016 (Diplopoda, Chordeumatida, Anthroleucosomatidae) from Georgia, Caucasus - Antić, Dragan; Margalitadze, Ana; Šević, Mirko (Zootaxa, 2025)
Four new, presumably troglobiotic species of the chordeumatidan genus Acanthophorella Antić & Makarov, 2016 are described from several Georgian caves. Acanthophorella didi sp. nov. and A. gaumarjos sp. nov. were discovered in three and one cave in the Racha karst massif, respectively, while A. eto sp. nov. and A. spinicoxa sp. nov. are known each from two caves in the Sataplia-Tskaltubo karst massif and Zemo Imereti plateau, respectively. All four species are properly diagnosed, described, and richly illustrated. Vulvae are described for the first time in Acanthophorella barjadzei Antić & Makarov, 2016, and new records are added for A. valerii Antić in Antić et al., 2023. Notes on the ecology and localities are given for new species. The distribution map and a key to all 10 species of the genus are presented. Distribution and troglomorphism within the genus are briefly discussed.